Expansion of assortment of functional gingerbread products - N. K. Lapteva; L. V. Mitkinykh (Аграрная наука Евро-Северо-Востока, 2019)
In order to expand the range of flour confectionary for healthy nutrition, documentation on new gingerbread products with increased food value was developed in 2017-2018. They are Prune gingerbread (kovrizhka) and gingerbread (pryanik) "Zabava", "Fantaziya", "Vdokhnovenie". The nutrition value of new gingerbread products is defined by the content of medium rye flour, sunflower oil, prunes, dried apricots, cocoa powder which enrich the products with many micronutrients necessary for a human body such as food fibers, mineral substances, vitamins, polyunsaturated fatty acids (PUFA). Prune gingerbread exceeds the production analog (Tula gingerbread) in the content of food fibers (3.6%), vitamin E (2.9 mg%) and vitamin B1 (0.11 mg%) by 2.25; 4.1 and 1.37 times, respectively. It also has more mineral substances (K, P, Ca, Mg, Fe) in comparison with the control - 2.0; 1.3; 1.4; 2.4; 1.4 times, respectively. Energy value of Prune gingerbread is 8.8% lower than that of the production analog (Tula gingerbread). In 100 grams of Prune gingerbread and gingerbreads "Zabava", "Fantaziya", "Vdokhnovenie" there are from 2.9 to 4.0 g of polyunsaturated linoleic acid that satisfy the minimum body need a day. Gingerbreads "Zabava", "Fantaziya", "Vdokhnovenie" exceed the production analog (gingerbreads “Festivalnye”) in the content of mineral substances (K, Ca, Mg, P, Fe) in total – by 46.4; 98.4; 45.0%, respectively; in food fibers – by 1.7-2.2 times; in vitamin E – by 1.9-2.0 times. New gingerbread products are functional as they contain 26.4-36.4% of average daily body need in PUFA and 29.0-37.0% of vitamin E. Gingerbreads 'Zabava' and 'Fantaziya' contain respectively 17.0 and 20.0% of average daily body need in food fibers and 15.7% – in iron.